The immunosuppressive phenotype of tumor-infiltrating neutrophils is associated with obesity in kidney cancer patients. (1st January 2020) - Margaroli, Camilla; Cardenas, Maria A.; Jansen, Caroline S.; Moon Reyes, Adriana; Hosseinzadeh, Fares; Hong, Gordon; Zhang, Yilin; Kissick, Haydn; Tirouvanziam, Rabindra; Master, Viraj A.
ABSTRACT: Infiltrating tumor neutrophils and myeloid-derived suppressor cells represent major populations in the tumor microenvironment that contribute to tumor progression. However, the phenotype of circulating and tumor-associated neutrophils, and the impact of cancer patients' metabolic state on neutrophil function need further characterization. Here we show that in kidney cancer patients, circulating neutrophils display an altered immature-like phenotype, and an activated/primed metabolic state. Circulating immature-like neutrophils acquire an activated phenotype upon migration into the tumor tissue, characterized by high expression of the immunosuppressive enzyme arginase-1, and active granule release. Interestingly, obesity and adipose tissue distribution were significantly associated with this activated phenotype of neutrophils, including the release of arginase-1 in the tumor tissue. These results provide a possible functional relationship between the metabolic status of the patients and disease progression, through an active immunosuppressive role of neutrophils within the kidney tumor microenvironment.